Legal Protection of Indonesian Citizens in Mixed-marriage with Rohingya Refugees - Allagan, Tiurma M. P.; Salfa, Salsabila; Sekarlangit, Agnes Galuh (Indonesian Journal of International Law, 2020)
There are 14 marriages that occurred between the Rohingyas and Indonesian citizens carried out in 2017. Only nine of them were reported to the refugees handling agency. Some have been made before coming to Indonesia and some after arrival. These situations resulted in legality problems of the marriage and its implications. The right to marry is fundamental in the life of human and is protected as human rights. However, Indonesia is not a signatory to the Convention on the Status of Refugees 1951 and has no legal mechanism to govern their marriages. Consequently, life for both asylum seekers and refugees is a relentless struggle and one of the significant challenges for them is in the area of marriage and family. This paper will discuss how Indonesian private international law provisions and the marriage law accommodate and protect the rights to marry stateless refugees in Indonesia. This paper primarily discusses the legal status of stateless persons and refugees amidst the lacuna in Indonesia. Noting the shift from the principle of nationality evident in case laws, this paper explores the possibility to use lex domicili as a surrogate connecting factor in determining the law applicable to stateless refugees’ personal status. In relation to marriage, subsequent validation (isbat nikah) could be the solution to ensure family unity. As the lack of valid documentation remains a challenge, the goodwill of the couple to enter into marriage and establish a family become the most important element.